A role for Sel-Plex™, a source of organic selenium in selenised yeast cell wall protein, as a factor that influences meat stability. (19th December 2016) - Edens, F. W.; Sefton, A. E.
Summary: Selenium is an important mineral required in the antioxidant system in animals, which is involved with oxidative stability in tissues, particularly membranes, and is involved in various aspects of meat quality and stability on the shelf, due to its protective properties on lipids, preventing rancidity. Se can be supplied in an inorganic or chemically organic form, and it is well known that the latter has beneficial properties and improved functionality in physiological systems compared to the former. Research has shown that organic Se is associated with increased tenderness and the prevention of certain problems in pale exudative meat, discolouration and off-flavours and odours in meat, although this depends on other components of the antioxidant system, such as vitamin E, being present as well. The change in prominence of glutathione peroxidase forms in their interaction with vitamin E in cell membranes is also noted. The following review (the third in a series) details the research that has been conducted into the role of Se in meat stability and related factors, with specific focus on organic forms of Se, namely the commercial product Sel-Plex ™ (Alltech Inc, Nicholasville, KY, USA), which is derived from yeast and in which selenium replaces sulphur in methionine forming selenomethionine in yeast protein.